Swine flu in Wikipedia in portuguese: analysis of the dynamics of editions and qualification of the contents of two articles - Esteves Gonçalves da Costa, Bernardo; d'Andréa, Carlos Frederico de Brito (Intexto, 2011)
This article intends to analyze and compare the collaborative edition of two articles about pandemic influenza A (H1N1) — or swine flu — in the Portuguese-language edition of Wikipedia. We have monitored the edits made in those articles during one month after they were created on April 25, 2009. We have characterized the edition of the texts and the dynamics of interactions among the editors. Additionally, we have analyzed their contents according to three criteria: authority, verifiability and timeliness.